2019
DOI: 10.1371/journal.pone.0212318
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microbial communities and mucosal gene expression in chicken intestines after galactooligosaccharides delivery In Ovo

Abstract: Intestinal mucosa is the interface between the microbial content of the gut and the host’s milieu. The goal of this study was to modulate chicken intestinal microflora by in ovo stimulation with galactooligosaccharides (GOS) prebiotic and to demonstrate the molecular responses of the host. The animal trial was performed on meat-type chickens (Ross 308). GOS was delivered by in ovo injection performed into the air cell on day 12 of egg incubation. Analysis of microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 103 publications
(123 reference statements)
1
75
0
1
Order By: Relevance
“…This would suggest that the impact of juvenile prebiotic feed is lifelong. Recently, Slawinska et al (48) have reported the delivery of galacto-oligosaccharides in ovo, which resulted in an increase in the relative abundance of Bifidobacterium-specific 16S rRNA PCRamplifiable sequences from the cecal contents of mature birds at 42 da, implying that the composition of the mature microbiota can be programmed in early development.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that the impact of juvenile prebiotic feed is lifelong. Recently, Slawinska et al (48) have reported the delivery of galacto-oligosaccharides in ovo, which resulted in an increase in the relative abundance of Bifidobacterium-specific 16S rRNA PCRamplifiable sequences from the cecal contents of mature birds at 42 da, implying that the composition of the mature microbiota can be programmed in early development.…”
Section: Discussionmentioning
confidence: 99%
“…Controls (the C group) were mock-injected with sterile physiological saline (n = 300, volume 0.2 mL/egg). Injection was carried out according to the in ovo procedure [32]. After hatching, the GOS and C groups were divided into two subgroups: maintained in thermoneutral condition (TN) and under the HS condition.…”
Section: Experimental Trial and Tissue Collectionmentioning
confidence: 99%
“…GOS that were delivered in ovo balanced the level of IL-10 and IL-12p40 to the baseline (under acute HS) or even down-regulated cytokine expression (under chronic HS). Previously, we have determined that GOS that were delivered in ovo increased the expression of the genes that are involved in the barrier function of the gut of broiler chickens [32]. An improved barrier function allows for a decrease of intestinal permeability due to stress and the influx of antigens into the milieu of the body [62].…”
Section: Immune-related Gene Expression Signaturesmentioning
confidence: 99%
See 2 more Smart Citations